Comparison of the effects of buprenorphine and methadone in combination with medetomidine followed by intramuscular alfaxalone for anaesthesia of cats undergoing ovariohysterectomy. Issue 2 (February 2020) - Mahdmina, Alaleh; Evans, Abigail; Yates, David; White, Kate L
Objectives: The aim of this study was to compare the quality of anaesthesia and analgesia between methadone and buprenorphine in combination with medetomidine after induction with intramuscular (IM) alfaxalone in cats undergoing ovariohysterectomy. Methods: Fifty-one female cats (American Society of Anesthesiologists status I–II), with a median age of 12 months (range 2–60 months), weighing a mean ± SD of 2.5 ± 0.5 kg, were recruited to the study. Cats were randomly allocated to receive medetomidine (600 µg/m 2 ) and buprenorphine (180 µg/m 2 ) (group MB) or medetomidine (500 µg/m 2 ) and methadone (5 mg/m 2 ) (group MM) IM. Anaesthesia was induced 15 mins later using alfaxalone (3 mg/kg) IM. Anaesthesia was maintained with isoflurane in oxygen. All cats received meloxicam preoperatively. Quality of premedication and induction and intraoperative physiological parameters were recorded. Atipamezole (50% of medetomidine dose) was administered at the end of surgery. Cats were assessed postoperatively by the same blinded observer using a simple descriptive scale, numeric rating scale, dynamic interactive visual analogue scale (DIVAS) and UNESP-Botucatu multidimensional composite pain scales, at 10, 20 and 30 mins post-extubation. Parametric and non-parametric data were compared using Student's t -test or Mann–Whitney U-tests, respectively. Results: Forty-one cats completed the study. No significant differences were detected between groups before or during anaesthesia. No cats required rescue analgesia. DIVAS scores at 10 mins were significantly less in the MM group compared with the MB. No differences between groups at any other time points were detected using the four metrology instruments. Conclusions and relevance: Both protocols provided good anaesthesia conditions for ovariohysterectomy in the cat.